1976
DOI: 10.4141/cjps76-011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dates of Seeding and Levels of N Fertilization on Yields, Chemical Composition and in Vitro Digestibility of Forage Kale

Abstract: Forage kale (Brassica oleracea L.) was seeded on three dates and fertilized at different levels of N as NH4NO3 for 3 yr. The highest dry matter (DM) yield was obtained with the earliest date of seeding and with levels of N fertilization of 120 kg/ha. The yield of crude protein (CP) was relatively constant among years, for the different dates of seeding and for N fertilization above 120 kg/ha. Increasing N fertilization or delaying seeding increased the leaf:stem ratio, and consequently the CP content. The leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 13 publications
4
22
0
Order By: Relevance
“…This may indicate that the early N treatment had more time to metabolise assimilated NO 3 into plant proteins and therefore NO 3 -N concentration was lower for these crops. The elevated NO 3 -N in the double N treatment was expected given the very high rates of N applied to this crop (Pelletier et al 1976;McDonald et al 1981;Fletcher et al 2010;Fletcher & Chakwizira 2012). We have, however, demonstrated that the timing of N fertilizer also had a marked impact on the NO 3 -N content of forage brassicas.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…This may indicate that the early N treatment had more time to metabolise assimilated NO 3 into plant proteins and therefore NO 3 -N concentration was lower for these crops. The elevated NO 3 -N in the double N treatment was expected given the very high rates of N applied to this crop (Pelletier et al 1976;McDonald et al 1981;Fletcher et al 2010;Fletcher & Chakwizira 2012). We have, however, demonstrated that the timing of N fertilizer also had a marked impact on the NO 3 -N content of forage brassicas.…”
Section: Resultsmentioning
confidence: 59%
“…Fertilizer nitrogen (N) is applied to increase forage brassica yields with the response depending on background soil N fertility and yield potential (Gramshaw & Crofts 1969;Pelletier et al 1976;McDonald et al 1981;Pearson & Thomson 1996;Wilson et al 2006;Fletcher et al 2007;Stevens & Carruthers 2008;Chakwizira et al 2009;Fletcher et al 2010;Chakwizira et al 2011;Keogh et al 2011). However, the application of fertilizer N that exceeds that required to obtain maximum crop yield can also result in the accumulation of elevated nitrate-nitrogen (NO 3 -N) in the plant (Pelletier et al 1976;McDonald et al 1981;Guillard & Allinson 1988;Jacobs & Ward 2008;Fletcher et al 2010;Fletcher & Chakwizira 2012). *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors attributed this rapid decline of CP to increasing DM accumulation rate and N dilution during this growth period. Other researchers concluded that the CP concentrations in the leaves of kale (B. oleracea L.) and turnips also declined with time (Pelletier et al, 1976;Reid et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This combination also provided the lowest moisture content feed and the highest in vitio digestibility and crude protein content. Changing Pelletier et al (1976) afi Fulkerson and Tossell (1972 …”
mentioning
confidence: 99%